Preliminary experience with pancreatic sphincterotomy as treatment for intraductal papillary mucinous neoplasm-associated recurrent pancreatitis - Bernardoni, Laura; Crinò, Stefano Francesco; De Conti, Giorgia; Conti Bellocchi, Maria Cristina; De Pretis, Nicolò; Amodio, Antonio; Frulloni, Luca; Gabbrielli, Armando (Endoscopy International Open, 2017)
Background and study aims Pancreatic intraductal papillary mucinous neoplasms (IPMN) are cystic tumors of the pancreas characterized by a malignant potential. IPMN have been associated with recurrent pancreatitis (RP). Obstruction of the main pancreatic duct by thick mucus has been postulated to be the cause of pancreatitis. In a few isolated reports, pancreatic sphincterotomy (PS) has been reported to reduce the frequency of pancreatitis. The aim of this study was to assess the efficacy of PS in patients with IPMN-associated RP.Patients and methods We retrospectively identified patients with RP and IPMN who underwent PS from June 2010 to December 2015. Patients were included in two different groups: (a) main duct/mixed type IPMN (MD-IPMN) and (b) branch duct IPMN (BD-IPMN) with or without worrisome features/high risk stigmata. Other causes of RP were excluded. The number of pancreatitis episodes occurring during a comparable time period before and after PS was evaluated. Results In total, 16 patients were analyzed (seven included in the MD-IPMN group and nine in the BD-IPMN group). The numbers of pancreatitis episodes occurring before and after PS were 3.5 ± 2.32 and 0.56 ± 1.03, respectively (P < 0.0001). Mean follow-up was 27.4 months (range 6 – 63 months). Complete, partial (reduction of pancreatitis episodes > 50 %), and no response were obtained in 11 (68.7 %), 3 (18.7 %), and 2 patients (12.5 %), respectively. One (6.25 %) case of mild post-endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis was observed. No cancer was detected in resected patients. None of the BD-IPMN group patients had or developed worrisome features/high risk stigmata during follow-up.Conclusions PS seems to be effective in reducing the number of episodes of IPMN-associated pancreatitis and should be considered as a treatment option in selected clinical settings. However, active surveillance should be continued considering the malignant potential of IPMN. Further prospective controlled studies are needed to confirm our results.